Pengaruh Promosi an Produk Terhadap Pengambilan Keputusan Memilih Madrasah - Imron Fauzi; Ari Kartiko (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research is to find out how far promotions and products influence decision making in choosing a madrasah. The variables in this study include promotion (X1) and product (X2) as independent variables, while decision making (Y) is the dependent variable or the variable being measured in this study. For the research method used in this study using quantitative methods with a survey approach with a total of 119 respondents. research data collection techniques using a questionnaire technique by distributing directly to respondents, while the way to select respondents using probability sampling random sampling approach or random samples. The data analysis technique used to test the research hypothesis uses multiple linear regression analysis techniques where before carrying out the test a prerequisite test is carried out first. To process research data using statistical tools 25. The results obtained showed that promotions and products have a positive and significant influence on the decision to choose a madrasa, while the variable that is more dominant in influencing the decision to choose a madrasa is the promotion variable.